A new species in the Cyrtodactylus intermedius (Squamata: Gekkonidae) group from an isolated limestone karst formation in southwestern Cambodia - Chhin, Sophea; Neang, Thy; Chan, Somaly; Kong, Kimsreng; Ou, Ratanak; In, Visatha; Samorn, Vireak; Sor, Ratha; Lou, Vanny; Sin, Sopha; Chhim, Meng; Stuart, Bryan L.; et al. (Zootaxa, 2024)
The gekkonid lizard Cyrtodactylus intermedius was formerly considered to be a single widespread species in hilly areas across eastern Thailand through southern Vietnam but has recently been partitioned into a complex of 12 nominal species across its range. A population belonging to the C. intermedius group was recently found in an isolated limestone karst block in Kampot Province in southwestern Cambodia, part of which lies within the recently designated Phnom Preah Kuhear Loung Natural Heritage Site. Comparisons of morphometric, meristic, qualitative morphological and color pattern data, as well as a molecular analysis using the mitochondrial ND2 gene, revealed that this population differs from all other named members of the C. intermedius group, and so is described here as a new species. The karst-dwelling C. regicavernicolus sp. nov. was recovered as the sister species to C. laangensis, the most geographically proximate member of the complex and one that is also restricted to a small limestone karst habitat.